Anti-oxidant effect of bergamot polyphenolic fraction counteracts doxorubicin-induced cardiomyopathy: Role of autophagy and c-kitposCD45negCD31neg cardiac stem cell activation. (June 2018) - Carresi, Cristina; Musolino, Vincenzo; Gliozzi, Micaela; Maiuolo, Jessica; Mollace, Rocco; Nucera, Saverio; Maretta, Alessia; Sergi, Domenico; Muscoli, Saverio; Gratteri, Santo; Palma, Ernesto; Bosco, Francesca; et al.
Abstract: Doxorubicin (DOXO) is one of the most widely used antineoplastic drugs. Despite its highly beneficial effects against several malignancies, the clinical use of DOXO is often associated to cardiomyopathy that leads to congestive heart failure. Here we investigated the antioxidant and cardioprotective effects of a polyphenol-rich fraction of citrus bergamot (BPF), in DOXO-induced cardiac damage in rats. Moreover, we evaluated the effect of BPF on cardiomyocyte survival and resident endogenous cardiac stem/progenitor cell (eCSC) activation. Adult male Wistar rats were i.p. injected with saline (serving as controls, CTRL, n = 10), BPF (20 mg/kg daily for 14 consecutive days, n = 10), DOXO (6 doses of 2, 5 mg/Kg from day 1 to day 14, n = 10), and DOXO + BPF (n = 10). Animals were then sacrificed 7 days later (i.e., at 21 days). DOXO administration reduced cardiac function at 21 days, an adverse effect significantly attenuated in animals receiving DOXO + BPF. No changes were detected in rats receiving just saline or BPF alone. The cardioprotective effect of BPF on DOXO acute toxicity was also associated with a significant antioxidant effect coupled with protective autophagy restoration, and attenuation of cardiomyocyte apoptosis and reactive hypertrophy. Finally, treatment of rats with BPF prevented eCSCs attrition by DOXO which was followed by a limited but significant increase of newly-formed BrdU + cardiomyocytes. In conclusion, BPF reduces DOXO-induced cardiotoxicity by counteracting reactive oxygen species (ROS) overproduction, thereby restoring protective autophagy and attenuating cardiomyocyte apoptosis and pathologic remodeling. This beneficial effects on the early toxicity of DOXO is associated with enhanced CSCs survival and regenerative potential. Overall these data point to a potential clinical role by diet supplementation with polyphenol-rich fraction of citrus bergamot in counteracting antracycline-induced cardiomyopathy. Highlights: Doxorubicin treatment represents the main cause of cardiomyopathy leading to heart failure in oncologic patients. Bergamot reduces doxo-induced cardiotoxicity by attenuating oxidative stress, apoptosis and restoring protective autophagy. Bergamot polyphenols supplementation promotes eCSC activation and cardiomyocyte replacement in doxo-injured cardiac tissue.